Temperature and Probe-to-Probe Variability Effects on the Performance of Capacitance Soil Moisture Sensors in an Oxisol - Fares, Ali; Safeeq, Mohammad; Awal, Ripendra; Fares, Samira; Dogan, Ahmet (WILEY, 2016)
Reliable and accurate monitoring of soil water content (theta) across the landscape is indispensable for many water resources applications. Capacitance-based in situ soil water content measuring devices are extensively used despite their sensitivity to soil properties besides water content, e.g., temperature and organic matter content. The main goals of this study were to: (i) examine the effects of temperature, hysteresis of the temperature response, and probe-to-probe variability on the performance of three (5TE, EC-5, and EC-TM) single capacitance sensors (SCS) in a Hawaiian Oxisol; and (ii) develop empirical calibration equations to correct for temperature and improve measurement accuracy. The SCS raw output and thermocouple temperature measurements were recorded at 1-min intervals during heating and cooling cycles between 1 and 45 degrees C. The three SCS and thermocouples were inserted in uniformly packed soils with theta varying from 0 to 0.55 m(3) m(-3). We used three probes for each SCS, and the entire experiment was replicated with two heating and cooling cycles. Temperature, hysteresis, and the probe-to-probe variability effects were highly significant (p 90% reduction in interquartile range) in measured water content due to changing soil temperature. Applying differing temperature corrections for heating and cooling did not improve the calibration any further.
Keywords: TIME-DOMAIN REFLECTOMETRY; WATER-CONTENT; ELECTRICAL-CONDUCTIVITY; CALIBRATION; FREQUENCY; VALIDATION; Environmental Sciences & Ecology; Agriculture; Water Resources